2003
DOI: 10.1038/sj.cdd.4401209
|View full text |Cite
|
Sign up to set email alerts
|

An MMP-2/MMP-9 inhibitor, 5a, enhances apoptosis induced by ligands of the TNF receptor superfamily in cancer cells

Abstract: Several studies have shown that matrix metalloproteases (MMPs) promote tumor growth, invasion, and metastasis. Consequently, MMP inhibitors have been developed as a new class of anticancer drugs, many of which are in clinical trials. The exact mechanism of the antineoplastic activity of MMP antagonists is unknown. To investigate the mechanism, we hypothesized that MMP inhibitors enhance the actions of apoptosis-inducing agents. To test this hypothesis, we treated breast, melanoma, leukemia, osteosarcoma, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Some studies have reported that MMPs promote tumor growth by releasing growth factors from their inactive membrane-bound form (Haro et al, 2000), thereby suggesting that MMP antagonists would inhibit cell growth. On the other hand, different studies have reported that MMPIs inhibit tumor proliferation by inducing apoptosis via the release of ligands such as TRAIL and TNFa from their membrane-bound inactive forms (Nyormoi et al, 2003). In a previous study, we demonstrated that adenoviral-mediated siRNA delivery of MMP-2 inhibited lung cancer growth and metastasis (Chetty et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that MMPs promote tumor growth by releasing growth factors from their inactive membrane-bound form (Haro et al, 2000), thereby suggesting that MMP antagonists would inhibit cell growth. On the other hand, different studies have reported that MMPIs inhibit tumor proliferation by inducing apoptosis via the release of ligands such as TRAIL and TNFa from their membrane-bound inactive forms (Nyormoi et al, 2003). In a previous study, we demonstrated that adenoviral-mediated siRNA delivery of MMP-2 inhibited lung cancer growth and metastasis (Chetty et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A combination therapy of MMP-inhibitor together with a cytotoxic drug seems to be a more attractive alternative. Some reports have indicated a synergistic effect of gelatinase selective inhibitors with apoptosis inducing agents in cell culture (Nyormoi et al, 2003). Animal models with a combination therapy have been promising, with reduced metastasis and increased survival (Haq et al, 2000;Yamamoto et al, 2003).…”
Section: Therapeutic Possibilities With the Mmp Inhibitorsmentioning
confidence: 99%
“…97 Tissue inhibitors of MMPs have been suggested to be useful in combination therapy with TRAIL because an MMP-2/ MMP-9 inhibitor caused reduced tumor growth and angiogenesis in nude mice. 98 However, the role of tissue inhibitors of MMPs in combination with TRAIL needs to be further investigated to determine the extent to which these molecules can overcome microenvironmentally induced resistance to TRAIL.…”
Section: Influence Of the Tumor Microenvironment On Trail-induced Apomentioning
confidence: 99%